Sirtuins and Insulin Resistance - Zhou, Shuang; Tang, Xiaoqiang; Chen, Hou-Zao (Frontiers in Endocrinology, 2018)
The mammalian Sirtuins (SIRT1-7) are an evolutionarily conserved family of NAD+-dependent deacylase and mono-ADP-ribosyltransferase. Sirtuins display distinct subcellular localizations and functions and are involved in cell survival, senescence, metabolism and genome stability. Among the mammalian Sirtuins, SIRT1 and SIRT6 have been thoroughly investigated and have prominent metabolic regulatory roles. Moreover, SIRT1 and SIRT6 have been implicated in obesity, insulin resistance, type 2 diabetes mellitus (T2DM), fatty liver disease and cardiovascular diseases. However, the roles of other Sirtuins are not fully understood. Recent studies have shown that these Sirtuins also play important roles in inflammation, mitochondrial dysfunction, and energy metabolism. Insulin resistance is the critical pathological trait of obesity and metabolic syndrome as well as the core defect in T2DM. Accumulating clinical and experimental animal evidence suggests the potential roles of the remaining Sirtuins in the regulation of insulin resistance through diverse biological mechanisms. In this review, we summarize recent advances in the understanding of the functions of Sirtuins in various insulin resistance-associated physiological processes, including inflammation, mitochondrial dysfunction, the insulin signaling pathway, glucose, and lipid metabolism. In addition, we highlight the important gaps that must be addressed in this field.